Analyzing the impact of strategy-based instruction on vocabulary acquisition and the listening skill - Abad Célleri, Mónica Patricia
This research was carried out with the intention of investigating the effect that explicit instruction of listening and vocabulary strategies had on third level university students of tourism. In order to fulfill this purpose, a qualitative study was conducted in which the following techniques were applied: a background questionnaire reflected the participants? educational background; a Strategy Inventory for Language Learning examined the learning strategies used by students when learning English and helped to design strategy instruction; nine lesson plans were developed to explicitly teach some top-down and bottom-up listening strategies and some vocabulary strategies as well; a strategy checklist revealed the strategies that were used by students after strategy instruction; and finally, a pre-test and post-test, a survey, and an interview were administered. The findings reflected that in fact, strategy instruction helped students improve vocabulary acquisition and listening which led to the conclusion that it is advisable to embed explicit strategy instruction in regular English programs.